Overview of fracture liaison services in the UK and Europe: standards, model of care, funding, and challenges. (9th June 2022) - Chesser, Timothy J.S.; Javaid, Muhammad Kassim; Mohsin, Zaineb; Pari, Carlotta; Belluati, Alberto; Contini, Achille; Caiaffa, Vincenzo; Chana-Rodríguez, Francisco; Gómez-Vallejo, Jesus; Sánchez-Pérez, Coral; Dailiana, Zoe H.; Stefanou, Nikolaos; et al.
Abstract : Abstract: Fragility fractures represent a growing global problem, including in the United Kingdom and European countries. Reports demonstrate the benefits of national guidance and organized fragility fracture programs through fracture liaison services to deliver care to patients who sustain these injuries. The challenge of assembling multidisciplinary teams, providing routine screening of appropriate patients, and monitoring therapies where there is a known compliance problem, remains an obstacle to the success of fragility fracture treatment programs to all. Efforts should continue to introduce and maintain fracture liaison services through coordinated national approaches and advanced systems.